Large-eddy simulation studies for predicting plume concentrations around nuclear facilities using an overlapping technique. (11th April 2019) - Nakayama, Hiromasa; Takemi, Tetsuya
We propose, in emergency response to nuclear accidents, a practical and quick local-scale atmospheric dispersion calculation method using an overlapping technique. First, we pre-calculated large-eddy simulations (LESs) of plume dispersion around an actual nuclear facility under idealised atmospheric conditions with 36 wind-direction cases and made a dataset of the 10-minute averaged concentrations for each wind direction case. Then, we conducted LESs of plume dispersion for 1-hour periods under realistic atmospheric conditions using the meteorological data and estimated the spatial distributions of the 1-hour averaged concentrations by overlapping the pre-calculated concentration data depending on the frequency of the mean wind directions. It is shown that the concentration distribution patterns are well reproduced in comparison to those under the realistic conditions. It is concluded that the atmospheric dispersion calculation method using the overlapping technique has potentially a high performance in emergency responses to nuclear accidents.